2022
DOI: 10.1002/ajhb.23743
|View full text |Cite
|
Sign up to set email alerts
|

Obese individuals do not underreport dietary intake to a greater extent than nonobese individuals when data are allometrically‐scaled

Abstract: Objective: The aim of this study was to assess the extent of misreporting in obese and nonobese adults on an absolute, ratio-scaled, and allometricallyscaled basis. Method: Self-reported daily energy intake (EI) was compared with total energy expenditure (TEE) in 221 adults (106 male, 115 female; age 53 ± 17 years, stature 1.68 ± 0.09 m, mass 79.8 ± 17.2 kg) who participated in a doubly-labeled water (DLW) subsection of 2013-2015 National Diet and Nutrition Survey. Data were log transformed and expressed as ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 54 publications
(85 reference statements)
0
22
0
Order By: Relevance
“…The AMPM method has been well validated (16,17), and the use of 2 separate recalls likely improved accuracy. In addition, it has been suggested that underreporting of energy intake is more common in people with obesity (39), although this has been brought into question (40). However, the perceived quality and quantity of dietary intake did not differ by obesity status (see Supplementary Table 12, Supplementary Digital Content 1, http://links.lww.com/AJG/C867), suggesting that, even if there is an obesity-driven bias in reported intake, it does not translate to bias in literacy or perception.…”
Section: Discussionmentioning
confidence: 99%
“…The AMPM method has been well validated (16,17), and the use of 2 separate recalls likely improved accuracy. In addition, it has been suggested that underreporting of energy intake is more common in people with obesity (39), although this has been brought into question (40). However, the perceived quality and quantity of dietary intake did not differ by obesity status (see Supplementary Table 12, Supplementary Digital Content 1, http://links.lww.com/AJG/C867), suggesting that, even if there is an obesity-driven bias in reported intake, it does not translate to bias in literacy or perception.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we recruited athletes who were already regularly, and voluntarily, tracking their diet and training so we could obtain longer-term longitudinal data across a variety of training regimens. Although dietary intake in the general population is likely to be under-reported [39], this would not necessarily apply to a population of athletes who are highly motivated and already in the habit of tracking dietary intake. It has been suggested that familiarity with and interest in keeping food records may lead to more reliable estimates of energy intake [40].…”
Section: Discussionmentioning
confidence: 99%
“…The most common method for self-reported dietary intake assessment was food records (nine studies), 16,18,19,21,[23][24][25][26][27] followed by 24-h recalls (eight studies), 17,20,[22][23][24][28][29][30] and food frequency questionnaires (two studies). 19,30 Svendsen and Tonstad 19 administered an original food frequency questionnaire via interview based on two existing questionnaires 31,32 that were designed to capture food intake over the previous 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies identified underreporters as below the 95% confidence interval of the ratio of reported energy intake to total energy expenditure. 34 Some studies 16,17,26,27 used multiple methods for comparing reported energy intake with energy expenditure. Waterworth et al 16 was unique among these studies in using both the ratio and allometric scaling methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation